2010
DOI: 10.1186/ar3131
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of myocardial abnormalities in rheumatoid arthritis using a comprehensive cardiac magnetic resonance approach: a pilot study

Abstract: IntroductionRheumatoid arthritis (RA) is a multi-organ inflammatory disorder associated with high cardiovascular morbidity and mortality. We sought to assess cardiac involvement using a comprehensive cardiac magnetic resonance imaging (cMRI) approach and to determine its association with disease characteristics in RA patients without symptomatic cardiac disease.MethodsRA patients with no history and/or clinical findings of systemic or pulmonary hypertension, coronary artery disease, severe valvular heart disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 46 publications
5
58
0
3
Order By: Relevance
“…Similar findings have been reported in other chronic inflammatory conditions such as rheumatoid arthritis. 25, 26 …”
mentioning
confidence: 99%
“…Similar findings have been reported in other chronic inflammatory conditions such as rheumatoid arthritis. 25, 26 …”
mentioning
confidence: 99%
“…Myocardial late enhancement on contrast-enhanced cardiac magnetic resonance (CMR) imaging occurs in myocardial areas of fibrosis [25]. A CMR imaging study in patients with RA without cardiovascular disease has shown findings that signify myocardial fibrosis in these patients [26,27]. Moreover, it has been reported that the underlying mechanism of diastolic dysfunction in the presence of normal systolic function is myocardial fibrosis [28].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study has shown that cardiac abnormalities indicating microvascular and macrovascular coronary ischemia, myocarditis, and/or myocardial fibrosis are frequent in asymptomatic patients with RA, as revealed by pharmacological stress perfusion and delayed-enhanced MRI 9 . Our present study has suggested that nonenhanced CMR with cine MRI, analyzing LV regional function, may be useful to detect subclinical myocardial involvement in RA.…”
Section: To the Editormentioning
confidence: 98%